1994
DOI: 10.3354/meps115243
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of tethered juvenile sea scallops Placopecten magellanicus in field experiments: effects of predators, scallop size and density, site and season

Abstract: The impact of predation on survival of juvenile sea scallops Placopecten magellanicus has important implications for the population dynamics and aquaculture of this species. In field experiments using tethered juvenile scallops, we examined the effect of biological and physical factors, such as prey size, predator and prey densitv, water temperature (season) and site, on mortality rates of scallops in Lunenburg Bay, Nova Scotia, Canada. The major predators of juvenile scallops were crabs Cancer irroratus and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 22 publications
1
43
2
Order By: Relevance
“…Tethering techniques have the shortcoming of potentially producing experimental artifacts that complicate meaningful ecological interpretation of results (Peterson and Black, 1994;Micheli, 1996;Curran and Able, 1998). Artefacts are generally related to interference of tethers with escape responses causing increased susceptibility to predators (Barbeau et al, 1994;Zimmer-Faust et al, 1994) or to tethers inducing behavioural changes in response to habitat which may make prey more or less susceptible to predators (Curran and Able, 1998). Peterson and Black (1994) also suggested that artifacts induced by tethering could be habitat dependent due to differences in predator assemblages.…”
Section: Refuge Value Of Habitatsmentioning
confidence: 99%
“…Tethering techniques have the shortcoming of potentially producing experimental artifacts that complicate meaningful ecological interpretation of results (Peterson and Black, 1994;Micheli, 1996;Curran and Able, 1998). Artefacts are generally related to interference of tethers with escape responses causing increased susceptibility to predators (Barbeau et al, 1994;Zimmer-Faust et al, 1994) or to tethers inducing behavioural changes in response to habitat which may make prey more or less susceptible to predators (Curran and Able, 1998). Peterson and Black (1994) also suggested that artifacts induced by tethering could be habitat dependent due to differences in predator assemblages.…”
Section: Refuge Value Of Habitatsmentioning
confidence: 99%
“…After 14 d , we noted whether scallops were living or dead, and in the latter case, whether the valves were crushed or intact. Crushed valves were assumed to result from decapod predation and intact valves from asteroid predation or other sources of mortality (Barbeau et al 1994, Stokesbury & Himmelman 1995. Vulnerability to predators was calculated as the proportion of scallops which had been preyed upon by each predator group.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the quality of animals, the success of seeding depends on the size of the juvenile and on the seeding season (Barbeau et al, 1994). The aim was to monitor the seeding stress of three batches of different sizes in three different seasons: spring, summer and autumn (winter seedings were not advised due to adverse weather conditions).…”
Section: Introductionmentioning
confidence: 99%